Empowering Inclusive Learning through Virtual Reality Using a Conceptual Framework for Digital Communication in Education (Open Society Conference, 2025)
The dynamic realm of digital communication is increasingly offering us the opportunity to transcend the barriers of tradition and create more inclusive, participatory learning environments. Virtual Reality (VR) is emerging as a powerful medium for this purpose. It holds immense potential for bridging learning gaps, particularly for communities that have been marginalized or otherwise excluded on the basis of geographical, social, or physical barriers. The immersive and interactive qualities of VR are instrumental in this transformative process. This paper explores the application of VR in fostering a more inclusive digital learning space. We specifically delve into how VR can enhance engagement, foster experiential understanding, and promote equal access to resources in educational settings. Drawing upon theoretical foundations from social constructivism and the principles of digital inclusion, we propose a hybrid framework. This framework leverages the potential of VR and digital communication strategies to create a more inclusive learning ecosystem. The paper discusses key dimensions including accessibility, immersion, interaction, and community-building. It also contemplates the broader implications of VR-powered learning in relation to overarching societal goals such as social equity and participatory inclusion. This paper, at its core, seeks to contextualize VR within the broader narrative of inclusive digital transformation, providing educators, policymakers, and technologists with valuable insights for building a fairer, more equitable digital learning future